The role of the eco–corridor for the walking beetles in Chupungryeong, Korea - Sung Nam Oh; Eun Young Choi; Jong Bong Choi; Eun Jeong Han; Dong Gul Woo; Jong Kyun Park (Journal of Asia-Pacific Biodiversity, 2022)
Eco–corridors are essential for walking wild animals to move and connect with ecosystems between fragmented habitats. This study aimed to determine the role of the eco–corridor and the biodiversity of ground beetles near eco–corridors constructed between areas divided for a prolonged period. As a center of the Chupungryeong eco–corridor, Bongsan–myeon, Gimcheon–si, Gyeongsangbuk–do on the Gyeongbu expressway, four sites were examined. To confirm the movement of beetles on the bridge, we used the capture–recapture method by marking specimens around 5 cm belonging to Carabus jankowskii, Eucarabus sternbergi, and Carabus semiopacus. On the other hand, pitfall traps in each opposite area were used to investigate the biodiversity of ground beetles. Our results indicated that ground beetles moved between separated habitats using eco–corridors. In addition, the collections showed different diversities at each site. These results confirmed the important role of the eco–corridor in walking animals, although more detailed research is required. Additionally, these results provide baseline data for future eco–corridor construction